Pengaruh Customer Relationship Management (CRM), Desain Produk dan Kualitas Pelayanan terhadap Kepuasan Pelanggan Swarovski Galaxy Mall Surabaya - Safitri, Elly Dwi; Pratiwi, Ni Made; Maduwinarti, Ayun (Universitas 17 Agustus 1945 Surabaya, 2021)
ABSTRACTCustomers are one of the valuable assets for the company, especially because loyal customers tend to have a fairly high commitment to the level of customer satisfaction. Maintaining customer satisfaction is not easy nowadays because there are many competitors in the same field. Thus, conditions like this make the company always evaluate feedback from customers so that the company can retain customers. So the author is interested in the research title